The Interplay of Liquidity, Investment Opportunities, and Corporate Social Responsibility on Banking Performance - Yura Karlinda Wiasa Putri (Universitas Pendidikan Nasional, 2026)
This study investigates the effects of liquidity, investment opportunity set (IOS), and corporate social responsibility (CSR) on the financial performance of banking firms in Indonesia during 2022–2024. Using secondary data drawn from audited annual reports and sustainability reports, this study analyzes a balanced panel of 135 bank-year observations from 45 banking companies listed on the Indonesia Stock Exchange. The hypotheses are tested using a fixed effect panel regression model with interaction terms to examine the moderating roles of IOS and CSR in the relationship between Loan to Deposit Ratio (LDR) and Return on Assets (ROA). The results show that LDR and IOS have a significant negative effect on ROA, while CSR has a significant positive effect on ROA. The interaction analysis further indicates that IOS positively moderates the effect of LDR on ROA, implying that higher IOS weakens the negative effect of LDR on profitability. In contrast, CSR negatively moderates the effect of LDR on ROA, indicating that higher CSR strengthens the negative effect of LDR on profitability. These findings suggest that bank profitability in the post-pandemic period is shaped not only by liquidity management and growth opportunities, but also by the way social responsibility interacts with lending intensity. This study contributes to the banking literature by providing recent evidence from an emerging market and by integrating financial and non-financial determinants of performance within a moderated panel-data framework.